Korelasi antara Penguasaan Kosakata, Minat Baca, dDan Kemampuan Meresepsi Cerpen Sufistik Siswa Madrasah Tsanawiyah Minahasa - Kinayati Djojosuroto (el Harakah: Jurnal Budaya Islam, 2014)
At Madrasah Tsanawiyah (MTs), literature is a part of Indonesian Letters and Language class. Literature can refine manners, enrich aesthetic experience, and improve the knowledge of students. Literature teaching increases their ability in understanding, enjoying, loving, and appreciating literary work, and also to help their development of psychological aspects towards shaping their character as a whole. Regarding reading interest, students were helped in understanding and comprehending sufi short story when they mastered the adequate vocabulary. The sufi short story as a work of literature is rich of life values, either local or spiritual ones. Sufi value  belongs to spiritual value  assessed to develop a person’s spiritual state. This study used the survey method with correlation technique. The respondents were tested on vocabulary mastery, given quiz for reading interest, and also taken essay test for the ability to comprehend sufi short story. It was done in MTs Kampung Jawa, Tondano, Minahasa.  Based on the analysis of the hypothesis test, all of the alternative hypothesizes (H1) given in this research were accepted. This means that the ability to comprehend sufi short story (Y) can be improved by developing the mastery of vocabulary (X1) and reading interest (X2). Di Madrasah Tsanawiyah (MTs), sastra merupakan bagian dari pelajaran Bahasa dan Sastra Indonesia. Sastra dapat memperhalus budi pekerti, memperkaya pengalaman estetik, dan meningkatkan pengetahuan siswa. Pengajaran sastra bertujuan untuk meningkatkan kemampuan siswa dalam memahami, menikmati, mencintai, dan menghargai karya sastra, serta membantu perkembangan aspekaspek kejiwaan anak menuju terbentuknya kebulatan pribadinya. Sehubungan dengan minat baca, siswa sangat terbantu dalam memahami dan meresepsi cerpen sufistik ketika mereka menguasai kosakata yang memadai. Cerpen sufistik sebagai karya sastra, kaya akan nilai-nilai kehidupan, baik itu nilai budaya maupun nilai spiritual. Nilai sufistik termasuk dalam nilai spiritual yang apabila dikaji akan membantu mengembangkan spiritual seseorang. Penelitian ini menggunakan metode survei dengan teknik korelasi. Responden diuji dengan tes penguasaan kosakata, kuis untuk minat baca, dan tes esai untuk kemampuan meresepsi cerpen sufistik. Penelitian ini dilaksanakan di MTs Kampung Jawa Tondano, Minahasa. Berdasarkan analisis pengujian hipotesis, dapat disimpulkan bahwa semua hipotesis alternatif (H1) yang diajukan pada penelitian ini diterima. Hal ini berarti bahwa kemampuan meresepsi cerpen sufistik (Y) dapat meningkat dengan meningkatkan penguasaan kosakata (X1) dan minat baca (X2).